2020
DOI: 10.1080/0361073x.2020.1766299
|View full text |Cite
|
Sign up to set email alerts
|

How an Age Simulation Suit affects Motor and Cognitive Performance and Self-perception in Younger Adults

Abstract: Background/Study Context: We assessed the influence of wearing an Age Simulation Suit (GERT) on gross motor, fine motor and cognitive performance in healthy young adults.Methods: In a within-subjects design, we tested 20 young adults (M age = 22.3 years) with and without the Age Simulation Suit. We assessed gross motor (Functional Fitness test) and fine motor (Purdue Pegboard test) functioning, cognitive performance (Digit Symbol Substitution test), and questionnaires on perceived physical state and mood.Gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Effects of GERT with full and low weight on performance of each physical activity task and associated psychological characteristics will be analyzed using a series of ANOVAS. Furthermore, it is examined whether the task 6MWT generates similar results as in other studies (e.g., Reference [18]). Differences in measurements and perceptions before and after performing the two tasks (6MWT and SCT) will be identified via repeated measures ANOVA.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 79%
See 3 more Smart Citations
“…Effects of GERT with full and low weight on performance of each physical activity task and associated psychological characteristics will be analyzed using a series of ANOVAS. Furthermore, it is examined whether the task 6MWT generates similar results as in other studies (e.g., Reference [18]). Differences in measurements and perceptions before and after performing the two tasks (6MWT and SCT) will be identified via repeated measures ANOVA.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 79%
“…Since a homogeneous group of participants is targeted, it is probable that a small number of participants already yields a significant and powerful result. As already described in Section 1, the proposed study design is inspired on the study by Vieweg and Schäfer ( [18]). Here, a group of 19 individuals (mixed gender) has proven to be sufficient.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the effects of cognitive status on physical performance, advancing age also has measurable effects on physical activity, performance, and functionality. A recent study assessed the effects of an age simulation suit on gross motor, fine motor and cognitive performance in healthy young adults and found that the age simulation suit reduced all three performances as well as mood and perceived physical state [ 63 ].…”
Section: Discussionmentioning
confidence: 99%